THE QUALITY OF EDUCATIONAL SERVICES TO PEOPLE WITH DISABILITIES - Еlena A. Khudorenko (Статистика и экономика, 2016)
The article discusses the current state of educational services for persons with disabilities. The author examines the levels of disability in the Russian Federation, the number of persons with disabilities, explores the characteristics of educational services to students with disabilities, and draws conclusions and makes recommendations.